Characteristic of the chemical composition of Artemisia pontica L. - Panasenko, O. I.; Mozul, V. I.; Denysenko, O. M.; Aksonova, I. I.; Oberemko, T. V.; Панасенко, Олександр Іванович; Мозуль, Валентина Іванівна; Денисенко, Ольга Миколаївна; Аксьонова, Ілона Ігорівна; Оберемко, Т. В.; Панасенко, А. И.; Мозуль, В. И.; et al. (Запорізький державний медичний університет, 2021)
The aim of this work is to determine the qualitative and quantitative characteristics of biologically active compounds of Artemisia pontica L. Definition prospects of medicinal herbal raw materials in the treatment of diseases. Materials and methods. Research material (Artemisia pontica L. herb) was collected in August 2019 in the Zaporizhzhia region, Ukraine. The tincture was obtained by maceration. So, the tincture was being extracted with methyl alcohol at room temperature for 10 days. The tincture was extracted with methyl alcohol at room temperature for 10 days according to the method of preparing tinctures. The study of the chemical composition of tincture of Artemisia pontica L. was carried out using gas chromatograph Agilent 7890B GC System (Agilent, Santa Clara, CA, USA) with mass spectrometric detector Agilent 5977 BGC/MSD (Agilent, Santa Clara, CA, USA) and chromatographic column DB-5ms (30 m × 250 mkm × 0.25 mkm). Results. 26 compounds were identified by analysis. Compounds such as n-hexadecanoic acid (16.71 %), 9,12,15-(Z,Z,Z)-octadecatrienoic acid (13.29 %), 2-(4a,8-dimethyl-7-oxo-1,2,3,4,4a,7-hexahydronaphthalen-2-yl)-propionic acid (8.80 %), 8-nitro-(1H)quinolin-4-ol-2-one (6.45 %) and neophytadiene (4.66 %) prevail in tincture. A literature review showed that n-hexadecanoic acid stimulates anti-inflammatory processes in human immune cells through TLR4 receptors, it has antitumor and antidiabetic activity and it also has anti-inflammatory effects. Derivatives of 9,12,15-(Z,Z,Z)-octadecatrienoic acid are used in diabetes therapy. 2-(4a,8-Dimethyl-7-oxo-1,2,3,4,4a,7- hexahydronaphthalen-2-yl)-propionic acid is an immunosuppressant and probably improves tissue insulin sensitivity. In addition, it is necessary to underline the presence of neophytadiene that has an anti-inflammatory effect. The presence of β-phellandrene provides insecticidal and eucalyptol anti-inflammatory effects. Conclusions. Considering the individual actions of the individual components, Artemisia pontica L. herb can be recommended for further research on its anti-inflammatory, antidiabetic, and antitumor effects.

Мета роботи – встановлення якісних і кількісних характеристик біологічно активних сполук Artemisia pontica L.; визначення перспектив використання лікарської рослинної сировини для лікування захворювань. Матеріали та методи. Матеріал для дослідження (Artemisia pontica L. трава) зібраний у серпні 2019 р. у Запорізькій області. Настойку одержували методом мацерації. Сировину екстрагували метиловим спиртом за кімнатної температури протягом 10 днів за способом приготування настойок. Хімічний склад настойки Artemisia pontica L. вивчали за допомогою газового хроматографа Agilent 7890B GC System (Agilent, Санта-Клара, Каліфорнія, США) з мас-спектрометричним детектором Agilent 5977 BGC/MSD (Agilent, Santa Clara, CA, США) та хроматографічної колонки DB-5ms (30 м × 250 мкм × 0,25 мкм). Результати. Під час аналізу встановили 26 сполук. У настойці переважали такі сполуки, як н-гексадеканова кислота (16,71 %), 9,12,15-(Z,Z,Z)-октадекатрієнова кислота (13,29 %), 2-(4a,8-диметил-7-оксо-1,2,3,4,4а,7-гексагідронафтален-2-іл)-пропіонова кислота (8,80 %), 8-нітро-(1Н) хінолін-4-ол-2-он (6,45 %) та неофітадієн (4,66 %). Огляд фахової літератури показав, що н-гексадеканова кислота стимулює протизапальні процеси в імунних клітинах людини через рецептори TLR4, має протипухлинну, протидіабетичну та протизапальну дії. Похідні 9,12,15-(Z,Z,Z)-октадекатрієнової кислоти використовують у терапії діабету. 2-(4a,8-диметил-7-оксо-1,2,3,4,4a,7-гексагідронафтален-2-іл)-пропіонова кислота є імунодепресантом і, ймовірно, поліпшує чутливість тканин до інсуліну. Необхідно підкреслити наявність неофітадієну, який має протизапальну дію. Наявність β-фелландрену та евкаліптолу забезпечує інсектицидну та протизапальну дії відповідно. Висновки. Враховуючи індивідуальні дії окремих компонентів, Artemisia pontica L. траву можна рекомендувати для наступних досліджень щодо її протизапальної, протидіабетичної та протипухлинної дії.

Цель работы – определение качественных и количественных характеристик биологически активных соединений Artemisia pontica L.; определение перспектив использования лекарственного растительного сырья для лечения заболеваний. Материалы и методы. Материал для исследования (трава Artemisia pontica L.) собран в августе 2019 г. в Запорожской области, Украина. Настойку получали путем мацерации. Сырье экстрагировали метиловым спиртом при комнатной температуре в течение 10 дней согласно методу приготовления настоек. Химический состав настойки Artemisia pontica L. изучали с помощью газового хроматографа Agilent 7890B GC System (Agilent, Санта-Клара, Калифорния, США) с масс-спектрометрическим детектором Agilent 5977 BGC/MSD (Agilent, Santa Clara, CA, США) и хроматографической колонки DB-5ms (30 м × 250 мкм × 0,25 мкм). Результаты. В ходе анализа установлены 26 соединений. В настойке преобладали такие соединения, как н-гексадекановая кислота (16,71 %), 9,12,15-(Z,Z,Z)-октадекатриеновая кислота (13,29 %), 2(4a,8-диметил-7-оксо-1,2, 3,4,4а,7-гексагидронафтален-2-ил)-пропионовая кислота (8,80 %), 8-нитро(1Н)-хинолин-4-ол-2-он (6,45 %) и неофитадиен (4,66 %). Обзор научной литературы показал, что н-гексадекановая кислота стимулирует противовоспалительные процессы в иммунных клетках человека через рецепторы TLR4, обладает противоопухолевым, противодиабетическим и противовоспалительным действиями. Производные 9,12,15-(Z, Z, Z)-октадекатриеновой кислоты используют в терапии диабета. 2(4a,8-диметил-7-оксо-1,2,3,4,4a,7-гексагидронафтален-2-ил)-пропионовая кислота – иммунодепрессант, вероятно, улучшает чувствительность тканей к инсулину. Следует отметить наличие неофитадиена, который обладает противовоспалительным действием. Наличие β-фелландрена и евкалиптола обеспечивает инсектицидное и противовоспалительное действие соответственно. Выводы. Учитывая индивидуальные действия каждого компонента, Artemisia pontica L. траву можно рекомендовать для дальнейших исследований на противовоспалительное, противодиабетическое и противоопухолевое действия.
Характеристика хімічного складу Artemisia pontica L.
Характеристика химического состава Artemisia pontica L.
Панасенко О. І. - ORCID ID: 0000-0002-6102-3455; Аксьонова І. І. - ORCID ID: 0000-0002-3534-700X.
Keywords: Artemisia pontica; chromato-mass spectroscopy; component composition; quantitative content; хромато-мас-спектроскопія; компонентний склад; кількісний вміст; хромато-масс-спектроскопия; компонентный состав; количественное содержание